2005
DOI: 10.1074/jbc.m412660200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of (S)-4,5-Dihydroxy-2,3-pentanedione, a Bacterial Signal Molecule Precursor, and Validation of Its Activity in Salmonella typhimurium

Abstract: We describe an original, short, and convenient chemical synthesis of enantiopure (S)-4,5-dihydroxy-2,3-pentanedione (DPD), starting from commercial methyl (S)-(؊)-2,2-dimethyl-1,3-dioxolane-4-carboxylate. DPD is the precursor of autoinducer (AI)-2, the proposed signal for bacterial interspecies communication. AI-2 is synthesized by many bacterial species in three enzymatic steps. The last step, a LuxS-catalyzed reaction, leads to the formation of DPD, which spontaneously cyclizes into AI-2. AI-2-like activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 43 publications
7
122
0
2
Order By: Relevance
“…Significantly, none of the above-mentioned studies attempted to use a defined preparation of AI-2 to restore the biofilm characteristics of the wild type. Very recently, however, De Keersmaecker et al (15) demonstrated that AI-2 derived from synthetic DPD could not restore biofilm formation by an S. enterica serovar Typhimurium luxS mutant, whereas introduction of luxS under the control of its own promoter complemented the defect. Similarly, addition of synthetic AI-2 failed to restore type III secretion and motility defects in enterohemorrhagic E. coli (60), phenotypes previously attributed to luxS/AI-2-based quorum sensing by Sperandio et al (57,58,59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, none of the above-mentioned studies attempted to use a defined preparation of AI-2 to restore the biofilm characteristics of the wild type. Very recently, however, De Keersmaecker et al (15) demonstrated that AI-2 derived from synthetic DPD could not restore biofilm formation by an S. enterica serovar Typhimurium luxS mutant, whereas introduction of luxS under the control of its own promoter complemented the defect. Similarly, addition of synthetic AI-2 failed to restore type III secretion and motility defects in enterohemorrhagic E. coli (60), phenotypes previously attributed to luxS/AI-2-based quorum sensing by Sperandio et al (57,58,59).…”
Section: Discussionmentioning
confidence: 99%
“…For S. enterica serovar Typhimurium, De Keersmaecker et al (15) showed that the addition of neither cysteine, methionine, SAM, nor DPD restored biofilm formation by a luxS mutant. Thus, it is unlikely that a lack of sulfur amino acids or extracellular DPD was responsible for this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A method for assaying biofilm formation of L. rhamnosus GG in vitro was optimized based on methods described previously by De Keersmaecker et al (15), with minor modifications. Briefly, biofilm formation on polystyrene pegs hanging into microtiter plate wells was assayed.…”
Section: Methodsmentioning
confidence: 99%
“…The Lsr ABC transporter is known to be involved in the detection and transport of AI-2 into the cell (Taga et al, 2001), while the rbs transporter has recently been suggested as an alternative AI-2 uptake system (Jesudhasan et al, 2010). A S. Typhimurium luxS deletion mutant was impaired in biofilm formation on polystyrene (De Keersmaecker et al, 2005;Jesudhasan et al, 2010). However, this phenotype could not be complemented by extracellular addition of QS signal molecules, suggesting that AI-2 is not the actual signal involved in Salmonella biofilm formation (De Keersmaecker et al, 2005).…”
Section: Cell-to-cell Communication In Salmonella Biofilms (Quorum Sementioning
confidence: 99%
“…A S. Typhimurium luxS deletion mutant was impaired in biofilm formation on polystyrene (De Keersmaecker et al, 2005;Jesudhasan et al, 2010). However, this phenotype could not be complemented by extracellular addition of QS signal molecules, suggesting that AI-2 is not the actual signal involved in Salmonella biofilm formation (De Keersmaecker et al, 2005). To this direction, Kint et al (2010) analyzed additional luxS mutants for their biofilm phenotype.…”
Section: Cell-to-cell Communication In Salmonella Biofilms (Quorum Sementioning
confidence: 99%